Facile Extraction of Natural Hydroxyapatite (HA) from Biowaste and Its Characterizations - Parajuli, Kshama; Panchen, Nicodemus; Gautam, Savya (Pragya Darshan प्रज्ञा दर्शन, 2023)
Natural Hydroxyapatite (HA) with chemical formula Ca10(PO4)6(OH)2 is a major mineral storage form of calcium and phosphorous in bone and it has been applied in many fields. In the present study, HA was extracted from biowaste; namely the buffalo bone by alkaline hydrolysis process followed by calcination at 900°C with holding time 6 hrs. in muffle furnace. The isolated material was analyzed by X-ray Diffraction (XRD), Fourier Transform Infra-Red Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM) etc. The SEM image suggested the isolated material had rod shaped and agglomerated. FTIR study indicated the phosphate and hydroxide were the major functional groups along with carbonate present in it. Further, XRD analysis inferred that the isolated material was only HA phased. The specific surface area of the isolated HA was determined by methylene blue adsorption method and it was found to be 141.12 m2 /g and pH point of zero charge (pHPZC) of the extracted biomaterial was determined to be 6.8 by pH the drift method. Thus the pure HA powder was synthesized by an environmentally friendly, cost effective method and may be applicable in many fields including waste water treatment and biomedicine etc.